Trend resistant designs for bioequivalence assessment of veterinary medicinal products - SAURAV, SUMEET; VARGHESE, CINI; JAGGI, SEEMA (The Indian Journal of Animal Sciences, 2020)
In veterinary medicinal trials, formulations are to be applied to the animals sequentially over time due to scarcity of homogeneous and healthy animals for experimentation, leading to carryover effects. Further, in such trials, many a times it may be required to compare some new (test) formulations to a previously well established (reference) formulation. Bioequivalence trials, using designs balanced for carryover effects, are advantageous for such situations. As experimental units are used sequentially over periods, there is a possibility that a systematic effect, or trend, influences the observations in addition to the experimental unit effect, formulation effect and carryover effect. Condition have been derived for designs for bioequivalence trials balanced for carryover effects to be trend-free and a method of constructing a class of such designs had also been developed. When trend effects are suspected, trend free designs are to be selected for experimentation and data need to be analyzed accordingly.